Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Team Games Tournament (TGT) Berbantuan Aplikasi Book Creator pada Pembelajaran Pendidikan Pancasila di Kelas IV SDN 120 Sukamaju Kota Jambi - Finestika, Shavira Kurnia; Fitria, Yanti; Reinita, Reinita; Iraqi, Hana Shilfia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe how to improve student learning outcomes in Pancasila education learning using the Team Games Tournament model assisted by the Book Creator application in class IV SDN 120 Suka Maju, Jambi City. This type of research is classroom action research (CAR) using two types of approaches, namely qualitative and quantitative approaches. This research was carried out in two cycles, with research procedures consisting of planning, implementation, observation, and reflection. The subjects of this study were class teachers as observers, researchers as practitioners or teachers, and 25 class IV students of SDN 120 Suka Maju, Jambi City. Data collection techniques in the form of observation analysis, tests and non-tests. The resulting data was analyzed in a quantitative descriptive manner. The results of the study showed that: First, the cycle I teaching module obtained an average of 85.4% (B), increasing in cycle II to 95.83% (SB). Second, the results of the implementation of the teacher aspect of cycle I obtained an average of 83.93% (B), increasing in cycle II to 96.42% (SB). Third, the results of the implementation of the student aspect of cycle I obtained an average of 82.14% (B), increasing in cycle II to 96.42% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 77.6 (C), increasing in cycle II to 91.5 (SB).